THE GENUS AESCHYNOMENE IN MALAYSIA (LEGUMINOSAE - PAPILIONATAE) - VELVA E. RUDD (BRIN Publishing (Penerbit BRIN), 1959)
Seven species are found to occur in Malaysia,only Ae.aspera presumably being native there.Key,synonymy, descriptions,and particulars are given, besides indexes to collections and names.Some twenty or more species of Aeschynomene have been attributed to Malaysia, or